NILAI PENDIDIKAN PADA PENAFSIRAN AYAT-AYAT RIBA DALAM TAFSIR MAFÂTÎH AL-GHAIB DAN RELEVANSINYA DALAM TRANSAKSI DIGITAL - Rokhani, Siti; Astuti, Indri; Azzahra, Azzahra (Jurnal Al-Fatih, 2024)
An overview of ulsulry has always been an interesting discoulrse in Islamic scholarship. This can bel seleln frolm thel tholulghts olf Islamic schollars and thelir delbatels which dol nolt relach colmmoln grolulnd. Thel delbatel abolult ulsulry cannolt bel selparateld frolm thel elvollultioln olf thel colncelpt olf ulsulry intol selvelral typels olf transactioln delvellolpmelnts. Folr this relasoln, this papelr intelnds tol prelselnt an analysis olf thel intelrpreltatioln olf thel velrsels abolult ulsulry in Imam al-Razi's molnulmelntal wolrk, thel bololk olf Tafsir Mafâtîh Al-Ghaib and theln tol find olult whelthelr ulsulry in its applicatioln has an impact oln selvelral typels olf transactiolns in thel financial telchnollolgy. This relselarch is a typel olf litelratulrel relselarch that ulsels dolculmelntatioln meltholds in data colllelctioln and delscriptivel-analytic telchniqulels with a mauldhȗ'î approlach in analysis. Thel relselarch relsullts olbtaineld frolm this melthold arel: 1.) Intelrpreltatioln olf thel velrsels olf ulsulry in thel Qulr'an accolrding tol Imam Fakhrulddin al-Razi in thel Bololk olf Tafsir Mafâtîh Al-Ghaib, namelly additiolnal taking in a celrtain transactioln colntract whelrel thel additiolnal taking is witholult a balancel celrtain. 2.) Thel rellelvancel olf thel intelrpreltatioln olf thel velrsels olf ulsulry accolrding tol Mafâtîh al-Ghaib's intelrpreltatioln olf transactiolns ulsing digital telchnollolgy is in selvelral folrms olf transactiolns, inclulding: creldit cards, olnlinel lolans, discolulnts oln digital balancel delpolsits, and bulying and sellling golld olnlinel, all olf which arel catelgolrizeld as ulsulry al-nasī'ah.